A Descriptor for Accurate Predictions of Host Molecules Enabling Ultralong Room‐Temperature Phosphorescence in Guest Emitters. (15th February 2022) - Chanmungkalakul, Supphachok; Wang, Chao; Miao, Rong; Chi, Weijie; Tan, Davin; Qiao, Qinglong; Ang, Esther Cai Xia; Tan, Choon‐Hong; Fang, Yu; Xu, Zhaochao; Liu, Xiaogang
Abstract: Although doping can induce room‐temperature phosphorescence (RTP) in heavy‐atom free organic systems, it is often challenging to match the host and guest components to achieve efficient intersystem crossing for activating RTP. In this work, we developed a simple descriptor Δ E to predict host molecules for matching the guest RTP emitters, based on the intersystem crossing via higher excited states (ISCHES) mechanism. This descriptor successfully predicted five commercially available host components to pair with naphthalimide (NA) and naphtho[2, 3‐c]furan‐1, 3‐dione (2, 3‐NA) emitters with a high accuracy of 83 %. The yielded pairs exhibited bright yellow and green RTP with the quantum efficiency up to 0.4 and lifetime up to 1.67 s, respectively. Using these RTP pairs, we successfully achieved multi‐layer message encryption. The Δ E descriptor could provide an efficient way for developing doping‐induced RTP materials. Abstract : A descriptor Δ E was developed based on the intersystem crossing via higher excited states (ISCHES) mechanism, allowing the accurate predictions of organic host–guest phosphorescent systems.